1847–48 Va. Acts 110, ch. 7, § 8 - (:unkn) unknown (General Publisher, 1847)
Created a fine for habitual conceal carrying of any pistol, dirk, Bowie knife, or weapon of the like kind. Fifty dollars
--
Keywords: CARRY - CONCEALED